MicroRNAs, long non-coding RNAs, and circular RNAs and gynecological cancers: focus on metastasis - Rezaee, Aryan; Ahmadpour, Sara; Jafari, Ameneh; Aghili, Sarehnaz; Zadeh, Seyed Saeed Tamehri; Rajabi, Ali; Raisi, Arash; Hamblin, Michael R.; Mahjoubin-Tehran, Maryam; Derakhshan, Marzieh (Frontiers in Oncology, 2023)
Gynecologic cancer is a significant cause of death in women worldwide, with cervical cancer, ovarian cancer, and endometrial cancer being among the most well-known types. The initiation and progression of gynecologic cancers involve a variety of biological functions, including angiogenesis and metastasis. Given that death mostly occurs from metastatic tumors that have invaded the surrounding tissues. Therefore, understanding the molecular pathways underlying gynecologic cancer metastasis is critical for enhancing patient survival and outcomes. Recent research has revealed the contribution of numerous non-coding RNAs (ncRNAs) to metastasis and invasion of gynecologic cancer by affecting specific cellular pathways. This review focuses on three types of gynecologic cancer (ovarian, endometrial, cervical) and three kinds of ncRNAs (long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and circular RNAs (circRNA)). We summarize the detailed role of non-coding RNAs in the different pathways and molecular interactions involved in the invasion and metastasis of these cancers.